Improving Class V Students' Indonesian Language Learning Outcomes Using the TPACK Approach - Kusbandiyah, Ani (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve the learning outcomes of students in the Indonesian language muple in grade V elementary school writing rhymes with the TPACK approach. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting was conducted with a post test to determine the development of students. In the first cycle, students who completed the post test were 78%. In the second cycle, students who completed the post test were 89%. In cycle III the students who completed after carrying out the post test were 100%. These results indicate that the TPACK approach can improve student learning outcomes, especially the Indonesian language muple, the material of writing rhymes for Class V at SDN 1 Sidabowa.